1998
DOI: 10.1901/jaba.1998.31-211
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Functional Communication Training With and Without Extinction and Punishment: A Summary of 21 Inpatient Cases

Abstract: Functional communication training (FCT) is a frequently used treatment for reducing problem behavior exhibited by individuals with developmental disabilities. Once the operant function of problem behavior is identified by a functional analysis, the client is taught to emit an appropriate communicative response to obtain the reinforcer that is responsible for behavioral maintenance. Studies on FCT have typically used small numbers of participants, have reported primarily on clients for whom FCT was successful, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
360
4
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(382 citation statements)
references
References 19 publications
13
360
4
5
Order By: Relevance
“…Hagopian et al (1998) describe typical implementation of a delay schedule. Participants were treated with FCT while on an inpatient hospital unit for the assessment and treatment of severe problem behavior.…”
Section: Delay Schedulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hagopian et al (1998) describe typical implementation of a delay schedule. Participants were treated with FCT while on an inpatient hospital unit for the assessment and treatment of severe problem behavior.…”
Section: Delay Schedulesmentioning
confidence: 99%
“…FCT has been demonstrated to be a highly effective treatment for individuals with intellectual disabilities, ranging from mild to profound, who engage in severe problem behaviors such as self-injury and aggression (e.g., Bailey, McComas, Benavides, & Lovascz, 2002;Carr & Durand, 1985;Fisher et al, 1993;Hagopian, Fisher, Sullivan, Acquisto, & LeBlanc, 1998;Kurtz, et al, 2003;Shirley, Iwata, Kahng, Mazaleski, & Lerman, 1997;Wacker et al, 1990). We searched and reviewed the published literature from 1985 to 2009 1 and identified 76 studies employing FCT as a treatment for 235 individuals with intellectual disabilities of varying ages (i.e., 2-34 years old) displaying a wide range of problem behavior (e.g., aggression, disruption, SIB, inappropriate sexual behavior).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we agree wholeheartedly that students need less aversive contingencies and more positive ones. However, it is impossible to ignore the empirical evidence demonstrating that punishment procedures can sometimes enhance the effectiveness of other procedures, especially if problem behaviors are severe (e.g., Hagopian, Fisher, Sullivan, Acquisto, & LeBlanc, 1998). Given that it is unlikely that schools will (or should) abandon punishment altogether, it would be helpful to provide some guidelines for situations that might warrant punishment, as well as specific guidelines for its ethical use.…”
Section: A Critical Look At the Contentmentioning
confidence: 99%
“…effective than programs that include reinforcement alone (Charlop-Christy & Haymes, 1996;Durand, 1982;Foxx & Azrin, 1972, Hagopian, Fisher, Sullivan, Acquisto, & LeBlanc, 1998. Individuals with developmental disabilities have a right to the most effective behavioral treatments available (Van Houten et al, 1988), however, so punishment procedures should be applied when clinically indicated.…”
mentioning
confidence: 99%